Algicidal activity of a novel bacterium, Qipengyuania sp. 3-20A1M, against harmful Margalefidinium polykrikoides: Effects of its active compound. (January 2023) - Ko, So-Ra; Le, Ve Van; Srivastava, Ankita; Kang, Mingyeong; Oh, Hee-Mock; Ahn, Chi-Yong
Abstract: Margalefidinium polykrikoides causes significant economic losses in the aquaculture industry by red tide formation. Algicidal bacteria have attracted research interests as a potential bloom control approach without secondary pollution. Qipengyuania sp. 3-20A1M, isolated from surface seawater, exerted an algicidal effect on M . polykrikoides . However, it exhibited a significantly lower algicidal activity toward other microalgae. It reduced photosynthetic efficiency of M . polykrikoides and induced lipid peroxidation and cell disruption. The growth inhibition of M . polykrikoides reached 64.9 % after 24 h of co-culturing, and expression of photosynthesis-related genes was suppressed. It killed M . polykrikoides indirectly by secreting algicidal compounds. The algicide was purified and identified as pyrrole-2-carboxylic acid. After 24 h of treatment with pyrrole-2-carboxylic acid (20 μg/mL), 60.8 % of the M . polykrikoides cells were destroyed. Overall, our results demonstrated the potential utility of Qipengyuania sp. 3-20A1M and its algicidal compound in controlling M . polykrikoides blooms in the marine ecosystem. Graphical abstract: Unlabelled Image Highlights: Qipengyuania sp. 3-20A1M showed selective algicidal activity against M . polykrikoides . Strain 3-20A1M damaged the photosystem apparatus in M . polykrikoides . Pyrrole-2-carboxylic acid was firstly determined as algicide to M . polykrikoides . Strain 3-20A1M could be a potential bacterial agent to control harmful algal blooms.